Perubahan Pilihan Santri Gresik Pada Pilpres 2019 - Avita Amelia; Dwi Krismawati; Moch Aji Setiawan; Retno Aprin Cahyani; Husna Suhada; Agus Machfud Fauzi (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2020)
Indonesia is a country that has a presidential government system with the president and deputy as the country's leaders. The head of state is responsible for regulating and establishing state policies for the better. The existence of a president and his deputy is elected through an election process. The presidential election in each region is certainly different from the various interesting phenomena in it such as in Gresik, which is famous for the nickname of the city of Santri. The purpose of this study was to determine the students' motives in Gresik in the presidential election in 2019. That is because in the 2014 presidential election in the Gresik region, Prabowo's candidate won a victory. However, in the 2019 presidential election Jokowi's candidate was the winner. The research method used in this research is descriptive qualitative. The research subjects in this study were students in the city of Gresik. Data collection instruments used in this study were in-depth interviews, literature study, and observation. The results of this study indicate that the voice change that occurred in the 2019 presidential election was due to the large influence of the vice president who was promoted by the Jokowi camp, Ma'ruf Amin because, it became a big consideration for the students in making choices. In addition, as Nahdliyin students there is a tradition in Islamic boarding schools to be obedient to their kiai.